The selective ROCK2 inhibitor KD025 reduces IL‐17 secretion in human peripheral blood mononuclear cells independent of IL‐1 and IL‐6. Issue 10 (21st September 2018) - Tengesdal, Isak W.; Kitzenberg, David; Li, Suzhao; Nyuydzefe, Melanie S.; Chen, Wei; Weiss, Jonathan M.; Zhang, Jingya; Waksal, Samuel D.; Zanin‐Zhorov, Alexandra; Dinarello, Charles A.
Abstract: Reducing the activities of the pro‐inflammatory cytokine IL‐17 is an effective treatment strategy for several chronic autoimmune disorders. Rho‐associated coiled‐coil containing kinase 2 (ROCK2) is a member of the serine‐threonine protein kinase family that regulates IL‐17 secretion in T cells via signal transducer and activator of transcription 3 (STAT3)‐dependent mechanism. We reported here that the selective ROCK2 inhibitor KD025 significantly reduced in vitro production of IL‐17 in unfractionated human peripheral blood mononuclear cells (PBMCs) stimulated with the dectin‐1 agonist Candida albicans . C. albicans induced IL‐17 was reduced by 70% ( p  < 0.0001); a similar reduction (80%) was observed in PBMC stimulated with the Toll‐like receptor 2 agonist Staphylococcus epidermidis ( p  < 0.0001). Treatment of PBMC with KD025 was not associated with a reduction in IL‐1β, IL‐6 or IL‐1α levels; in contrast, a 1.5 fold increase in the level of IL‐1 receptor antagonist (IL‐1Ra) was observed ( p  < 0.001). KD025 down‐regulated C. albicans ‐induced Myosin Light Chain and STAT3, whereas STAT5 phosphorylation increased. Using anti‐CD3/CD28 activation of the TCR, KD025 similarly suppressed IL‐17 independent of a reduction in IL‐1β. Thus, ROCK2 directly regulates IL‐17 secretion independent of endogenous IL‐1 and IL‐6 supporting development of selective ROCK2 inhibitors for treatment of IL‐17‐driven inflammatory diseases. Abstract : ROCK2 targeting bypasses IL‐1 signaling and regulates C. albicans –induced IL‐17 secretion by modulating STAT3/STAT5 phosphorylation in human PBMCs. In contrast, IL‐1Ra inhibits IL‐17 secretion by blocking intracellular IL‐1 signaling via STAT3‐independent manner, underlying different molecular mechanisms involved in regulation of IL‐17 production induced by C. albicans .